Mucociliary Clearance Differs in Mild Asthma by Levels of Type 2 Inflammation - Corcoran, Timothy E.; Huber, Alex S.; Hill, Sherri L.; Locke, Landon W.; Weber, Lawrence; Muthukrishnan, Ashok; Heidrich, Elisa M.; Wenzel, Sally; Myerburg, Mike M. (Chest, 2021)
Although mucus plugging is a well-reported feature of asthma, whether asthma and type 2 inflammation affect mucociliary clearance (MCC) is unknown. Does type 2 inflammation influence mucus clearance rates in patients with mild asthma who are not receiving corticosteroids? The clearance rates of inhaled radiolabeled particles were compared between patients with mild asthma with low (n = 17) and high (n = 18) levels of T2 inflammation. Fraction exhaled nitric oxide (Feno) was used to prospectively segregate subjects into T2 Lo (Feno < 25 ppb) and T2 Hi (Feno > 35 ppb) cohorts. Bronchial brush samples were collected with fiber-optic bronchoscopy, and quantitative polymerase chain reaction was performed to measure expression of genes associated with T2 asthma. MCC rate comparisons were also made with a historical group of healthy control subjects (HCs, n = 12). The T2 Lo cohort demonstrated increased MCC when compared with both T2 Hi and historic HCs. MCC within the T2 Hi group varied significantly, with some subjects having low or zero clearance. MCC decreased with increasing expression of several markers of T2 airway inflammation (CCL26, NOS2, and POSTN) and with Feno. MUC5AC and FOXJ1 expression was similar between the T2Lo and T2Hi cohorts. Increasing T2 inflammation was associated with decreasing MCC. High rates of MCC in T2 Lo subjects may indicate a compensatory mechanism present in mild disease but lost with high levels of inflammation. Future studies are required to better understand mechanisms and whether impairments in MCC in more severe asthma drive worse clinical outcomes. [Display omitted]